Espaços de governança territorial na Amazônia: análise sobre o conselho de desenvolvimento territorial do baixo Tocantins – Pará - RIBEIRO, Nayara Viana (Universidade Federal do Pará, 2021)
This study aimed to investigate Territorial Governance elements in the Council of Territorial Development of the Lower Tocantins, Pará, and its implications for unleashing territorial development processes. For this, there was documentary analysis of the first territorial plan for sustainable rural development in the Lower Tocantins, as well as participation in board meetings. The results show that the Council of Territorial Development of the Lower Tocantins, is its structure in a Territorial Governance space in the Amazon, however, it appears that this new governance, has yet to deploy new territorial development processes.